The Other Wes Moore Guide for English 100 - Kansas State University, K-State First (Kansas State University. K-State First., 2015)
Developed for English 100: Expository Writing, this guide to "The Other Wes Moore" by Wes Moore was designed to meet the course's objective of examining diverse communities and identities in the United States with the rhetorical concerns of writing for different audiences and purposes. Included in the guide is a short timeline, excerpts, and writing prompts.
Keywords: First-year seminars; First-year experience program; English 100; Common reading program; Guide; The Other Wes Moore; Brochures